Thermophysical Property Measurement using Containerless Levitation Techniques in Microgravity and Terrestrial Environments - Nawer, Jannatun. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Anil Saigal, Luis Dorfmann, and Takehiko Ishikawa.; Keyword: Mechanical engineering.